Gender Identity: Transgender - Korichi, Abderrazak (جامعة الوادي - University of Eloued, 2020)
Third gender people include individuals whose gender identity, gender expression or behavior do not typically conform to the sex they were assigned at birth, While the term “Transgender” is commonly accepted, not all gender-diverse individuals self-identify as transgender, Since researches have been found out, transgender’s visibility and community have grown considerably, This paper, therefore, seeks to shed light upon how gender identity, sexual orientations, and their interactions are represented in the lived experiences of the transgender people, and which attempts to establish the reliability and the validity of the gender identity disorder, starting by providing with a full literature review about the concept of transgenderism followed by a section of research methodology based on quantitative method and relied on a questionnaire submitted to this specific social category of people in order to collect data and then formulating a discussion about the results gained by using SPSS program for the analysis of the findings and finally, drawing a general conclusion.
مقال
Keywords: الهوية الجنسية; الجنسالمتحولين جنسيا; ا لأفراد من الجنس الثالث; التعبير بين الجنسين; Gender Identity; Sex; Transgender; Individuals; Third gender people; Gender expression